Exploring the proteome associated with the mRNA encoding the D1 reaction center protein of Photosystem II in plant chloroplasts. (16th January 2020) - Watkins, Kenneth P.; Williams‐Carrier, Rosalind; Chotewutmontri, Prakitchai; Friso, Giulia; Teubner, Marlene; Belcher, Susan; Ruwe, Hannes; Schmitz‐Linneweber, Christian; van Wijk, Klaas J.; Barkan, Alice
Summary: Synthesis of the D1 reaction center protein of Photosystem II is dynamically regulated in response to environmental and developmental cues. In chloroplasts, much of this regulation occurs at the post‐transcriptional level, but the proteins responsible are largely unknown. To discover proteins that impact psbA expression, we identified proteins that associate with maize psbA mRNA by: (i) formaldehyde cross‐linking of leaf tissue followed by antisense oligonucleotide affinity capture of psbA mRNA; and (ii) co‐immunoprecipitation with HCF173, a psbA translational activator that is known to bind psbA mRNA. The S1 domain protein SRRP1 and two RNA Recognition Motif (RRM) domain proteins, CP33C and CP33B, were enriched with both approaches. Orthologous proteins were also among the enriched protein set in a previous study in Arabidopsis that employed a designer RNA‐binding protein as a psbA RNA affinity tag. We show here that CP33B is bound to psbA mRNA in vivo, as was shown previously for CP33C and SRRP1. Immunoblot, pulse labeling, and ribosome profiling analyses of mutants lacking CP33B and/or CP33C detected some decreases in D1 protein levels under some conditions, but no change in psbA RNA abundance or translation. However, analogous experiments showed that SRRP1 represses psbA ribosome association in the dark, represses ycf1 ribosome association, and promotes accumulation of ndhC mRNA. As SRRP1 is known to harbor RNA chaperone activity, we postulate that SRRP1 mediates these effects by modulating RNA structures. The uncharacterized proteins that emerged from our analyses provide a resource for the discovery of proteins that impact the expression of psbA and other chloroplast genes. Significance Statement: To discover proteins involved in the post‐transcriptional regulation of the chloroplast psbA gene, we employed several methods to comprehensively analyze proteins that associate with maize psbA mRNA in vivo. Functional analyses of three top candidates revealed a putative RNA chaperone that impacts the expression of the chloroplast psbA, ndhC, and ycf1 genes, and two RNA Recognition Motif (RRM) domain proteins that bind psbA mRNA but have little effect on psbA expression under the growth conditions sampled.